DAMPAK RETURN ON EQUITY DAN DIVIDEND PAYOUT RATIO TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Perbankan di BEI) - Surtikanti -; Andina Halidya Artha (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
The global economic crisis that occurred in 2008 have an impact on Indonesia's capitalmarkets, especially in the banking sector, as reflected in falling stock prices declined. Theseconditions affect the firm value because the company itself can be measured through the company'sstock price The purpose of this research is to empirically study effect of Return on Equity anddividend payout ratio either partially or simultaneously toward firm value.Population of this research are banking firm that list in Indonesia Stock Exchange during 2006to 2010. The sample used purposive sampling method and result six banking firms that used assamples in this research. To determine return on equity, dividend payout ratio and firm value,purposive sampling technique used. Data were taken from companies balance sheet, incomestatement, and notes of financial statement. Then return on equity, dividend payout ratio and firmvalue were analyzed with quantitative approach the multiple linear regression to determine theinfluence either simultaneously or partially.Based on the results of descriptive statistical analysis, partially and simultaneously return onequity and dividend payout ratio have a significant effect on firm value.